AN ANALYSIS OF SPEECH ACT DURING SPEAKING CLASS ACTIVITY (TEACHER – STUDENTS TALKS) - Rachmawati, Chintya Fitria; Rustandi, Andi; Thoyyibah, Luthfiyatun (English Education and Applied Linguistics Journal (EEAL Journal), 2022)
Abstract.This research focuses on speech acts as a significant role in teaching and learning process. In line with this topic, the aim of this research is to find out the types of speech act mostly used by teachers’ and students’ English program. This study used descriptive qualitative method. The data used were the utterances performed by the teacher and students talk in speaking class. Those speech acts are supported by theories of Searle & Suherdi (1976), who find out the use of speech act. From the theory, there are 5 classifications of illocutionary speech act; representative,directive, expressive, commissive, and declarative. The findings show that the classifications of speech acts mostly used by teacher is directive while representative is mostly used by the students. From the findings, teacher’s directive has some involvement toward students’ behavior during teaching and learning process. Besides, the use of representative by students has enhanced their speaking ability. This study concludes that when teacher and students used the speech acts, it helpsthem comprehend the message in every utterance and easy to understand when communication. Hopefully, this study will help develop good classroom communication between teachers and students.